SOCIAL-PSYCHOLOGICAL DETERMINANTS OF FORMING AN ACTIVE CIVIC POSITION AMONG YOUTH IN THE CONTEXT OF NEW UZBEKISTAN: THE ROLE OF MANAGERIAL DECISION-MAKING - Azamat S. Nazarov (American Journals Publishing, 2025)
In the context of New Uzbekistan, the formation of an active civic position among youth has become a strategic priority for sustainable social development and effective public governance. This article examines the social-psychological determinants influencing the development of civic engagement among young people, with particular emphasis on the role of managerial decision-making in educational, social, and institutional settings. Drawing on social-psychological theories of social influence, value orientation, identity formation, and motivation, the study analyzes how leadership decisions and management practices shape youth civic consciousness and participation.The research highlights the significance of evidence-based managerial decisions, participatory governance, and youth-oriented policies in fostering civic responsibility, social initiative, and democratic values. Special attention is given to the interaction between individual psychological factors and institutional management mechanisms within the framework of ongoing reforms in New Uzbekistan. The findings suggest that effective managerial decision-making acts as a key mediating factor that enhances the impact of social-psychological conditions on the formation of an active civic position among youth. The article concludes by emphasizing the need to integrate social-psychological insights into youth policy and management strategies to strengthen civic engagement and social stability.
Keywords: Youth civic engagement; social-psychological factors; active civic position; managerial decision-making; leadership psychology; public governance; New Uzbekistan